Study of the Effect of Mulching Materials on Weed Control in Saffron Cultivation in Eastern Morocco - Ibtissam Mzabri; Maria Rimani; Khadija Charif; Nourddine Kouddane; Abdelbasset Berrichi (The Scientific World Journal)
Saffron (Crocus sativus L.) is cultivated in many countries for its culinary and medicinal values. The production of saffron is limited by several factors, including weed infestation, which causes damage to the crop in terms of quantity and quality. However, little information is available on the different weed management strategies for saffron cultivation, as most of the strategies implemented are developed for large-scale and conventional agriculture. As a result, they are not applicable or affordable for organic or smallholder farmers, as is the case for saffron cultivation. The objective of this study is to compare the effectiveness of plastic mulching versus mulching in controlling weeds in saffron cultivation in the eastern region of Morocco. During the trial, which was conducted in 2018, the parameters measured correspond, on the one hand, to morphometric measurements and determination of saffron stigma yield and, on the other hand, to the determination of density, dry biomass, and weed control capacity. Compared to the control, mulching reduced the population and dry biomass of the most formidable weeds such as Cynodon dactylon, Aster squamatus, Cyperus rotundus, and Convolvulus arvensis. The average stigmata yield from plastic mulch treatment was 9% higher than of the control, and the number of leaves, leaf area, number, weight, and percentage of daughter corms with large diameter were higher for plants grown under mulch. Overall, the results of this study showed that the use of PE (polyethylene) mulch effectively reduced weed populations and improved saffron yield and vegetative growth.